Effects Of Leader-Member Exchange, Interpersonal Relationship, Individual Feeling Of Energy And Creative Work Involvement Towards Turnover Intention: A Path Analysis Using Structural Equation Modeling - Adil, Muhammad Shahnawaz; Awais, Ayesha (Asian Academy of Management (AAM), 2016)
This study investigates the impact of leader-member exchange (LMX), interpersonal relationship, individual feeling of energy and creative work involvement on turnover intention. A sample of 300 respondents is drawn from the manufacturing sector of Karachi. Confrmatory factor analysis is used to assess the reliability and validity of the measurement model. Structural equation modeling method was applied to test the six hypotheses. The results show that interpersonal relationship is positively related with turnover intention. LMX is positively related with individual feeling of energy which is in turn, positively related with creative work involvement. Moreover, LMX is found negatively related with turnover intention. In particular, LMX and creative work involvement have shown an insignifcant impact on interpersonal relationship and turnover intention respectively. The managerial implications and areas for future research are discussed.